Down-regulation of β-lactam antibiotics resistance and biofilm formation by Staphylococcus epidermidis is associated with isookanin - Ren, Qiang; Luo, Wanhe; Chi, Haoming; Zhang, Lili; Chen, Wei (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Biofilm formation is the major pathogenicity of Staphylococcus epidermidis (S. epidermidis), which enhances bacterial resistance to antibiotics. Isookanin has potential inhibitory activity on biofilm. Method The inhibiting mechanisms of isookanin against biofilm formation through surface hydrophobicity assay, exopolysaccharides, eDNA, gene expression analysis, microscopic visualization, and molecular docking were explored. Additionally, the combination of isookanin and β-lactam antibiotics were evaluated by the broth micro-checkerboard assay. Results The results showed that isookanin could decrease the biofilm formation of S. epidermidis by ≥85% at 250 μg/mL. The exopolysaccharides, eDNA and surface hydrophobicity were reduced after treatment with isookanin. Microscopic visualization analysis showed that there were fewer bacteria on the surface of the microscopic coverslip and the bacterial cell membrane was damaged after treatment with isookanin. The down-regulation of icaB and up-regulation of icaR were observed after treatment with isookanin. Additionally, the RNAIII gene was significantly up-regulated (p < 0.0001) at the mRNA level. Molecular docking showed that isookanin could bind to biofilm-related proteins. This indicated that isookanin can affect biofilm formation at the initial attachment phase and the aggregation phase. The FICI index showed that the combination of isookanin and β-lactam antibiotics were synergistic and could reduce doses of antibiotics by inhibiting biofilm formation. Discussion This study improved the antibiotic susceptibility of S. epidermidis through inhibition of the biofilm formation, and provided a guidance for the treatment of antibiotic resistance caused by biofilm